Simulation on Emotion Recognition for Autism Therapy - Adzmi, Muhammad Azrin (Universiti Teknologi PETRONAS, 2017)
This paper mainly focusing on the simulation of emotion recognition software based on the Local Binary Pattern (LBP) algorithm to extract the features from the image. The program will be used by the therapist during therapy session with the autism child in order to create more exciting environment for them to learn about the classification of basic human emotions with the help of human-computer interaction. Automated facial expression analysis is an exciting and challenging trouble, and impacts critical applications in many regions which includes human–computer interaction and information-driven animation. Deriving an effective facial representation from authentic face snap shots is an essential step for a success facial features reputation. On this paper, we empirically evaluate facial representation based totally on statistical local functions, neighborhood Binary styles, for person-independent facial expression recognition. Distinctive system gaining knowledge of strategies are systematically examined on numerous databases.